Sibling conflict and dishonest signalling in birds - Caro, S; West, S; Griffin, A (National Academy of Sciences, 2016)
Offspring survival can often depend on successful communication with parents about their state of need. Theory suggests that offspring will be less likely to honestly signal their need when they experience greater competition, from either a greater number of nestmates or less-related nestmates. We found support for this hypothesis with a comparative analysis, examining data from across 60 species of birds. We found that offspring are less honest about their level of need when: (1) they face competition from current siblings; (2) their parents are likely to breed again, and so they are in competition with future siblings; and (3) parental divorce or death means that they are likely to be less related to future siblings. More generally, these patterns highlight the sensitivity of communication systems to conflict between signaller and receiver, while also suggesting that when there is little conflict, natural selection favours the honest.